The joint impact of corporate governance mechanisms and corporate social responsibility practices on the performance of Malaysian listed companies - Karim, Sitara (2020)
The financial crises over the past two decades revealed severe shortcomings in corporate governance (CG) mechanisms and corporate social responsibility (CSR) practices globally. Malaysia also suffered the same fate when many organizations experienced weak compliance of CG codes and CSR practices. Given this condition, this study investigated the joint impact of CG mechanisms and CSR practices on the performance of Malaysian listed companies representing 5501 firm-year observations for the period 2006-2017. Furthermore, this study examined the moderating effect of board characteristics on the relationship between CG-CSR and performance relationship. Dynamic panel regressions were utilized assuming that CG-CSR and performance relationships are encountered with dynamic endogeneity and reverse causality; thus, system-GMM provides efficient solutions for such econometric problems. The findings reveal that CG and CSR, mainly, have value destroying impacts on firm performance such that CEO duality, directors’ remunerations, RMC independence, board diversity, environment, community, and workplace practices of CSR negatively and significantly affect firm performance consistent with agency theory predictions and agency cost argument. Contrarily, RMC size, RMC meetings, and marketplace practices of CSR positively determine firm performance parallel with resource dependence theory and the risk management perspective of CSR. Moreover, firm size positively, and leverage negatively affect firm performance. Additionally, ownership structure variables, CEO remuneration, board size, board independence, and money spent on CSR do not affect performance. Besides, an insignificant moderating effect of board characteristics is observed on the CG-CSR and performance relationship. Not with standing sound theoretical support, practically, the findings imply that despite continuous amendments in the Malaysian Code of Corporate Governance (MCCG), an effective monitoring mechanism is required to assess the compliance of the Code and CSR framework provided by the Securities Commission Malaysia and Bursa Malaysia. Thus, Malaysian listed companies should ensure compliance with the Code and CSR framework to attain better performance.